Kritik Sosial Pada Lirik Lagu Baepsae/Silver Spoon Karya BTS (Analisis Wacana Kritis Norman Fairclough) - Zulhani, Hilda; Mayasari, Mayasari; Poerana, Ana Fitriana (Jurnal Ilmiah Wahana Pendidikan, 2025)
Music is not only a medium of entertainment, it is also a means through which a singer can convey messages to listeners. Through song lyrics, listeners can understand the meaning that the singer or songwriter wants to express. Songs can also be used as a medium for delivering criticism, whether it be criticism of economic policies or sensitive issues occurring in the social environment. For instance, the song Baepsae/Silver Spoon by BTS contains a call for addressing social issues within society. The purpose of this study is to determine the social criticism contained in the lyrics of Baepsae/Silver Spoon using Norman Fairclough's critical discourse analysis method, which comprises three dimensions, text, discourse practice, and socio-cultural practice. The results of this study indicate that at the text level, the lyrics contain innuendo and allusions to convey criticism. At the discourse practice level, it is evident that the song lyrics are based on social problems present in society. At the sociocultural practice level, it is explained that this song can represent the younger generation who feel marginalized.i